Treatment-Related Adverse Events of Combination Immune Checkpoint Inhibitors: Systematic Review and Meta-Analysis - Park, Robin; Lopes, Laercio; Cristancho, Cagney R.; Riano, Ivy M.; Saeed, Anwaar (Frontiers in Oncology, 2020)
Background: Although clinical practice guidelines for the management of Immune Checkpoint Inhibitors (ICI)-related adverse events have recently been published, precise and nuanced toxicity data for combination ICI therapy is lacking. Therefore, herein we have conducted a systematic review and meta-analysis of published clinical trials on combination ICI to synthesize the treatment-related adverse event profile of combination ICI therapy. Methods: PUBMED, EMBASE, and Cochrane Database/EBM were searched for eligible studies. Clinical trials evaluating combination immune checkpoint inhibitor therapy in advanced unresectable cancer were included in the analysis based on prespecified criteria. Risk of bias across studies was evaluated using the Begg’s funnel plot and Egger’s regression test. Summary outcomes were pooled risk ratios (RR) and the logit transformed proportion for incidence data. Results: A total of 18 studies comprising 2767 patients across 10 cancer types were included in the final analysis. Combination ICI was associated with a slightly higher risk of all-grade adverse events (RR 1.07 [95% CI 1.03-1.11]) and markedly greater risk of grade 3 or higher adverse events (RR 2.21 [95% CI 1.57-3.10]) compared to monotherapy ICI. Subgroup analyses showed significant differences in risk of grade 3 or higher adverse events between treatment type (PD-1+CTLA-4 and PD-L1+CTLA-4), among cancer types, and among dosing regimens (N1I3, N3I1 and D20T1). Incidence of all-grade adverse events was 0.905 [95% CI 0.842-0.945] and grade 3 or higher events/all-grade adverse events was 0.396 [95% CI 0.315-0.483]. The most common all-grade TRAEs were diarrhea/colitis, fatigue/asthenia, nausea/vomiting, rash, and pruritis. Conclusion: Combination ICI therapy has a significantly different treatment-related adverse event profile compared to monotherapy.